Case Report: Corneal Leucoma as a Novel Clinical Presentation of Nail-Patella Syndrome in a 5-Year-Old Girl - Hou, Ling; Du, Yue; Wu, Yubin; Zeng, Yue; Zhao, Chengguang (Frontiers in Pediatrics, 2021)
Nail-patella syndrome (NPS) is a rare autosomal-dominant disorder characterized by the classic tetrad of absent or hypoplastic finger and toe nails, absent or hypoplastic patella, skeletal deformities involving the elbow joints, and iliac horns. This disease is caused by heterozygous pathogenic variations in the LMX1B gene, which encodes the LIM homeodomain transcription factor protein (LMX1B). We report a case of corneal leucoma and dysplasia prior to overt steroid-resistant nephrotic syndrome (SRNS) in a patient with NPS. At presentation, the parents of a 5-year-old female patient reported their daughter had corneal leucoma, psychomotor delay and speech defect. We also noted the presence of bilateral edema of the lower extremities, hypertension, nail dystrophy, and the bilateral absence of patella. She developed steroid-resistant nephrotic syndrome. Lowe oculocerebrorenal syndrome and NPS were the conditions considered in differential diagnosis. Trio-based whole genome sequencing indicated a heterozygous de novo likely pathogenic variation in the LMX1B gene (c.805A>C [p.Asn269His]). Patients with NPS often develop nail, ocular, or orthopedic symptoms prior to nephrotic syndrome. Corneal leucoma may be a novel clinical presentation of NPS.